1991
DOI: 10.1139/f91-018
|View full text |Cite
|
Sign up to set email alerts
|

Relation between Mercury Concentrations in Walleye (Stizostedion vitreum vitreum) and Northern Pike (Esox lucius) in Ontario Lakes and Influence of Environmental Factors

Abstract: We examined the relation between mercury levels in walleye (Stizostedion vitreum vitreum) and northern pike (Esox lucius) in Ontario lakes. Walleye and northern pike occurred together in 79 of the 346 study lakes. The length-standardized mercury concentrations in coexisting walleye and northern pike in the 79 lakes were highly correlated (r2 = 0.60). The mean mercury concentrations in walleye and northern pike of standardized length from these lakes were 0.65 and 0.52 μg/g, respectively. Lacustrine characteris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
36
1
2

Year Published

1993
1993
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(44 citation statements)
references
References 13 publications
5
36
1
2
Order By: Relevance
“…As with the Hg concentrations in rnacroinvertebrates, mean Hg concentrations in the muscle of 1-kg northern pike were elevated in the acidic dystrophic lakes ( Fig. 2; Table 1), which is in accordance with results from more comprehensive studies showing that Hg concentrations in northern pike and other fish usually correlate positively with lake dystrophy and acidity Verta et al 1986;Hikanson et al 1990a;Wren et al 1991).…”
Section: Watt?? Chemistrysupporting
confidence: 82%
“…As with the Hg concentrations in rnacroinvertebrates, mean Hg concentrations in the muscle of 1-kg northern pike were elevated in the acidic dystrophic lakes ( Fig. 2; Table 1), which is in accordance with results from more comprehensive studies showing that Hg concentrations in northern pike and other fish usually correlate positively with lake dystrophy and acidity Verta et al 1986;Hikanson et al 1990a;Wren et al 1991).…”
Section: Watt?? Chemistrysupporting
confidence: 82%
“…A great percentage of it is removed by biological processes, what consequently cause a microbial growth and a consumption of the oxygen dissolved in the liquid mass (Wren et al 1991;Jordão et al 2002). The measured oxygen values in the sampling sites of Piracicaba River by the present study were similar to the ones obtained from Oberdá in (1996).…”
Section: Resultssupporting
confidence: 85%
“…Animals of sedentary nature or little mobility tend to present a bigger amount of the element than the migrators, regarding its time to the metal exposition (Verta 1990). In the same way, the ones that occupy the higher trophic levels, in special the carnivorous fish accumulate a higher amount in their tissues (Olson et al 1973;Wren et al 1991). For the studied Geophagus brasiliensis, the perceived amount seems to be determined by the action of these factors.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…When oxygen is limited, inorganic Hg may be released from binding with oxyhydroxide compounds of iron and manganese and thereby increase the pool of Hg 2+ available to methylating bacteria (Chadwick et al, 2006), which may in turn be more abundant in anoxic conditions (Morel et al, 1998;Ullrich et al, 2001;Fleming et al, 2006). A few studies have demonstrated a positive relationship between dissolved iron and Hg in fish such as yellow perch (Gabriel et al, 2009), northern pike (Esox lucius), and walleye (Sander vitreus; Wren et al, 1991). However, it is not clear whether this is due to similar biogeochemical transport and cycling of Hg and iron, or a greater abundance of iron-reducing, Hg-methylating bacteria in water with high dissolved iron content.…”
Section: Bioavailability In Aqueous Environmentsmentioning
confidence: 99%